The image of exemplary woman in medieval korean literature: based on the composition “Sleep in a jade pavilion” (Journal of Oriental Studies, 2018)
The composition discusses the influence of literary and artistic models to the moral and humanisticcharacteristics of medieval korean women. The matter of women and standpoint to the women in theworld of Korea in the middle Ages was one of the most difficult questions at that time. Versatile images ofwomen gives us an opportunity to understand the special features of korean ethnos. Through analyzingthe composition “Sleep in a jade pavilion” by unknown author, we tried to depict the national conceptof the confucian ideal image of woman.